English gerund-participial clauses and their Macedonian equivalents - Gj. Atanasovska, Katarina; Cvetkoski, Vladimir (Slavia Centralis, 2022)
Gerund-participle constructions in English are used widely and have different functions. They are structurally varied, and they appear in diverse contexts. This paper deals with English non-finite gerund-participle clauses from a formal and functional point of view. The contrastive analysis of English and Macedonian examples examines their Macedonian translation equivalents as well. The aim of the paper is to draw a parallel between the two languages with regard to non-finite gerund-participle clauses, and to offer some insights into the similarities and differences between the two languages. The findings show that English gerund-participle constructions are expressed in Macedonian in a rich variety of ways, such as: In most cases, Macedonian equivalents include verbal adverbs (the -јќи form of the verb), noun and preposition combinations, as well as various finite and non-finite structures.
Keywords: non-finite gerund-participial clauses; present participle; -ing clauses; form; function; translation equivalent